Teachers’ Reflective Thinking during Remote Learning in SMP N 2 Tejakula - Ni Luh Dian Puspa Dewi; Putu Ngurah Wage Myartawan; Ni Putu Astiti Pratiwi (STKIP AGAMA HINDU SINGARAJA, 2022)
This study was aimed at investigating reflective thinking teachers during remote learning in SMP Negeri 2 Tejakula and the problems that they encounter in which it was viewed from the English teachers’ perceptions. Descriptive Quantitative Study was used as a research design of this study which involved the English teachers of SMP Negeri 2 Tejakula as the participants. The data were obtained through survey and interview. English teachers’ self-reflected questionnaire by Choy et al (2017) was adapted in conducting the survey. The results of this study showed that the English teachers show a positive response toward the questionnaire in which it was also found that there were four skills used in the reflective thinking during remote learning in SMP Negeri 2 Tejakula. Then, this research found that the teachers’ problem was due to the low insight of the teachers in using online application where the students gave bad comments because the teachers ignored students’ feedback in the application